A new ATP-independent DNA endonuclease from Schizosaccharomyces pombe that recognizes cyclobutane pyrimidine dimers and 6-4 photoproducts. - Bowman, K K (1994)
We have discovered a new DNA endonuclease in the fission yeast Schizosaccharomyces pombe which recognizes cyclobutane pyrimidine dimers and (6-4) pyrimidine-pyrimidone photoproducts. S. pombe DNA endonuclease (SPDE) catalyzes a single ATP-independent incision immediately 5' to the UV photoproduct and generates termini containing 3' hydroxyl and 5' phosphoryl groups. Based on these properties, we propose that SPDE may function in a DNA repair capacity, representing the initial recognition/cleavage step of a DNA excision repair pathway.